Evaluation and comparison of shear bond strength of porcelain to a beryllium-free alloy of nickel-chromium, nickel and beryllium free alloy of cobalt-chromium, and titanium: An in vitro study - Ananya Singh; Keerthi Ramachandra; Achut R Devarhubli (Wolters Kluwer Medknow Publications, 2017)
Aims: The aim of this study was to evaluate and compare the shear bond strength of porcelain to the alloys of nickel-chromium (Ni-Cr), cobalt-chromium (Co-Cr), and titanium. Materials and Methods: A total of 40 samples (25 mm × 3 mm × 0.5 mm) were fabricated using smooth casting wax and cast using Ni-Cr, Co-Cr, and titanium alloys followed by porcelain buildup. The samples were divided into four groups with each group containing 10 samples (Group A1-10: sandblasted Ni-Cr alloy, Group B1-10: sandblasted Co-Cr alloy, Group C1-10: nonsandblasted titanium alloy, and Group D1-10: sandblasted titanium alloy). Shear bond strength was measured using a Universal Testing Machine. Statistical Analysis Used: ANOVA test and Tukey's honestly significance difference post hoc test for multiple comparisons. Results: The mean shear bond strength values for these groups were 22.8960, 27.4400, 13.2560, and 25.3440 MPa, respectively, with sandblasted Co-Cr alloy having the highest and nonsandblasted titanium alloy having the lowest value. Conclusion: It could be concluded that newer nickel and beryllium free Co-Cr alloys and titanium alloys with improved strength to weight ratio could prove to be good alternatives to the conventional nickel-based alloys when biocompatibility was a concern.